PRODUCTIVITY OF OATS AND SPRING BARLEY DEPENDING ON PREDECESSORS AND USE OF MICRO-FERTILIZERS IN NORTHERN STEPPE - Гирка, А. Д.; Кулик, І. О.; Андрейченко, О. Г. (Scientific Progress & Innovations, 2013)
The results of studying the influence of the use of fertilizers on crop yield of oats and spring barley in the Northern Steppe. It is established, that a complex application of micro seed treatment and spraying of crops provides increased productivity of oats by 10%, barley – 15% depending on the predecessor. Found that more adapted to arid conditions are oats that provided by 0.72 t per ha (30.9%) higher yield than barley. The best predecessor for these crops are winter wheat, cultivation after which ensured grain yield formation of oats by 10.1 and 18.1%, and barley – by 20.4 and 23.7% more than after maize for forage and sunflower respectively.